About forensic phonetics - Hollien, Harry (Linguistica (Ljubljana), 2012)
This article sets forth the goals and content of Forensic Phonetics and its major elements. Considered are 1) the processing and analysis of spoken utterances, 2) enhancement of speech intelligibility (re: surveillance and other recordings), 3) authentication of recordings, 4) speaker identification, and 5) detection of deception, intoxication, and emotions in speech. Stress in speech, and the psychological stress evaluation systems that some individuals attempt to use as lie detectors also will be considered.
Keywords: analiza glasu; analyse de la voix; forenzična fonetika; govorci; identification du locuteur; identifikacija; linguistique juridique; phonétique juridique; sodna lingvistika